2017
DOI: 10.1016/j.cities.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Smart cities: Utopia or neoliberal ideology?

Abstract: This paper develops a critical understanding of the smart city by investigating the values and ideas that underpin this concept and how they are translated into practice. It suggests that, despite private companies and municipalities promoting the smart city as a revolutionary utopia, this utopia is, on the contrary, an expression of the neoliberal ideology. The case study of the Italian city of Genoa shows that the smart city utopia acts as a generator of a collective imaginary while promoting the interests o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
206
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(215 citation statements)
references
References 46 publications
2
206
0
7
Order By: Relevance
“…The label 'smart city' appears most frequently in the literature, and by a very large margin, although this popularity is very recent. The possible explanation for this recently evolved popularity could be that this term might be much more politically and technologically neutral; it includes also social and sustainable dimensions; and it represents some sort of utopia that could easily be applauded given the positive connotation of the word 'smart' per se (see also Eremia et al, 2017;Grossi & Pianezzi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The label 'smart city' appears most frequently in the literature, and by a very large margin, although this popularity is very recent. The possible explanation for this recently evolved popularity could be that this term might be much more politically and technologically neutral; it includes also social and sustainable dimensions; and it represents some sort of utopia that could easily be applauded given the positive connotation of the word 'smart' per se (see also Eremia et al, 2017;Grossi & Pianezzi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the sustainability argument has evacuated the politics of the possible, the radical contestation of alternative future socioenvironmental possibilities and socio-natural arrangements, and silences the radical antagonisms that are constitutive of our socionatural orders by externalizing conflict. (Swyngedouw, 2007: 26) For a growing body of critical literature, The Smart City is understood as 'the technological version of a sequence of neoliberalinfused new urban visions' (Kitchin, 2015: 132), whereby existing trajectories of capitalist growth are reinforced as the primary means for driving urban development (Cugurullo, 2018;Grossi and Pianezzi, 2017;Viitanen and Kingston, 2014). Innovation in The Smart City is, therefore, mostly limited to technological and digital advancements rooted in market-economic logics, while foreclosing more general socio-political innovation (Taylor Buck and While, 2017;White, 2016).…”
Section: The Smart City: the Critiquementioning
confidence: 99%
“…For instance, the Manchester smart city initiative in air quality monitoring is a typical example of a climate change agenda that aims to reinvigorate the need to adopt new technologies/techniques for urban sustainability governance while stimulating economic growth [33]. Moreover, Grossi and Pianezzi [34] reported that Genoa is partnering with Toshiba and Selex to deploy smart city solutions to address the challenges of hydrological instability in order to reduce the potential for future emergencies in the area. In the area of waste management, North American cities, such as Boston, Seattle, Pittsburgh, and New York, are integrating the smart city concept into the Open311 non-emergency digital platform for real-time urban maintenance services [35].…”
Section: The Environmental Sustainability Perspectivementioning
confidence: 99%